2020
DOI: 10.1002/jmv.26360
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency as a potential culprit in critical COVID‐19 patients

Abstract: Background: As an immune modulator, vitamin D has been implicated in the coronavirus disease-2019 (COVID-19) outcome. We aim to systematically explore the association of vitamin D serum levels with COVID-19 severity and prognosis. Methods: The standardized mean difference (SMD) or odds ratio and 95% confidence interval (CI) were applied to estimate pooled results from six studies. The prognostic performance of vitamin D serum levels for predicting adverse outcomes with detection of the best cutoff threshold wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
143
1
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 30 publications
8
143
1
11
Order By: Relevance
“…However, since no causal treatment for COVID-19 is available, identification of modifiable prognostic factors may help to improve outcomes. Our results corroborate previous reports [22,23] on VitD as a potential determinant of disease severity supporting assessment of VitD status in all SARS-CoV-2 infected individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, since no causal treatment for COVID-19 is available, identification of modifiable prognostic factors may help to improve outcomes. Our results corroborate previous reports [22,23] on VitD as a potential determinant of disease severity supporting assessment of VitD status in all SARS-CoV-2 infected individuals.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the available literature, D'Avolio et al showed that 25(OH)D concentrations were lower in patients with positive PCR for SARS-CoV-2 [21], proposing VitD supplementation as a useful measure to reduce the risk of infection. In a recently published meta-analysis, which included mostly patient data from non-peer-reviewed sources, a prognostic relevance of VitD was suggested arguing that diagnosis of VitD deficiency could be a helpful adjunct in assessing patients' potential of developing severe COVID-19 [22]. Notably, Faul et al [23] in their study on 33 patients with SARS-CoV-2-related pneumonia reported that VitD deficiency (baseline 25(OH)D < 12 ng/mL) was associated with a significantly increased risk for IMV, which appears in line with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was underpowered to detect a mortality difference between deficient and replete groups, the significant findings were that patients with lower concentrations of 25OH-D (≤ 30 nmol/l) at the time of acute infection demonstrated clinically relevant, elevated markers of cytokine release syndrome and were more likely to become hypoxic and require ventilatory support. Our data compliment emerging evidence that vitamin D status may be a surrogate prognosticator for morbidity and mortality [3].…”
supporting
confidence: 89%
“…Vitamin D Improving the physical barriers of the body by regulating the production of proteins for tight junctions [50], adherens junctions [51], and gap junctions [52] Stimulating the production of antimicrobial peptides, such as cathelicidin and defensins [55] Modulating T helper (Th) cell responses to induce a shift from Th1 to Th2 responses [61,62,64] Preventing cytokine storms by decreasing inflammatory cytokines [67,68] and nuclear factor κB (NF-κB) activation [69] Inverse correlation between vitamin D level and viral respiratory tract infection [38][39][40] Vitamin D deficiency/insufficiency observed in patients with COVID-19 [41] Inverse correlation between COVID-19 mortality and sunlight exposure [45] or vitamin D level [43,48] Worse prognosis in COVID-19 patients with a low level of vitamin D [47,49] Selenium Preventing mutations in viral genome [71][72][73] Increasing CD4 + T cell activation, proliferation, and differentiation; inducing Th1 phenotype [74] Enhancing the function of cytotoxic effector cells by increasing the cytotoxicity of CD8 + T cells and lytic activity of natural killer (NK) cells [77] Maintaining T cell maturation and functions, including T cell-dependent antibody production [79,80] Preventing vasoconstriction and blood coagulation [87], which may increase COVID-19 mortality [81] Higher selenium level in surviving COVID-19 patients compared to deceased patients [16] Higher recovery rate from COVID-19 in patients with higher selenium levels [17] Author Contributions: Conceptualization: H.K. ; investigation, writing, and original draft preparation: M.B.…”
Section: Consequences Of Deficiency/effects Of Supplementation In Infmentioning
confidence: 99%